2019
DOI: 10.2322/tastj.17.363
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Time Orbit Raising of Geostationary Spacecraft by Optimizing Feedback Gain of Steering Law

Abstract: This study considers the minimum time orbit-raising problem of geostationary spacecraft with low-propulsion thrusters. This problem is equivalent to determining an appropriate thrust direction during orbit raising. This study proposes a closedloop thruster steering law that determines the thrust direction based on the optimal feedback gains and control errors of each orbital element. The feedback gains of the steering law are assumed to be the functions of orbital elements and are optimized by a meta-heuristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For example, the Sequential quadratic programming (SQP) method [7] and Particle swarm optimization method [8] have been proposed to optimize the transfer time. These solutions require complicated orbit and attitude control, but few studies have demonstrated an acceptable method of attitude control.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Sequential quadratic programming (SQP) method [7] and Particle swarm optimization method [8] have been proposed to optimize the transfer time. These solutions require complicated orbit and attitude control, but few studies have demonstrated an acceptable method of attitude control.…”
Section: Introductionmentioning
confidence: 99%